ANTITUMOR EFFECT OF ELECTROMAGNETIC FIELDS AND THEIR EFFECT ON PAIN IN EXPERIMENTAL AND CLINICAL ONCOLOGY - E. M. Frantsiyants; E. A. Sheiko (Исследования и практика в медицине)
The review examined and analyzed scientific publications on the effect of electromagnetic fields (EMF) on various systems of the human body and animals with tumors, as well as on pain in the experiment and the clinic. The theoretical foundations and practical results of the use of EMF in various modulations and modes in the goals and objectives of oncology, including how to optimize the process of anesthesia and correct the vital activity of the body's functional systems with a tumor, are consecrated. Information is given on possible physicochemical effects, features, and mechanisms of therapeutic influence at various levels of a living organism. The ability of electromagnetic waves to transfer information both within a single biosystem and at the level of a whole living organism with a tumor is shown. Studies of combined action of EMF and chemotherapy were analyzed. It has been established that there are experimental prerequisites for using this factor in order to induce changes in the permeability of the membranes of tumor cells by increasing the internalization of chemotherapeutic agents and, thus, enhance the antitumor effect. The role of EMF in the induction of apoptosis in tumor cells is shown. It has been shown that chemotherapy together with electromagnetic fields induces apoptosis and has an inhibitory effect on DNA synthesis in osteosarcoma cells, breast cancer, colon cancer, melanoma and other tumors. The role of magnetic fields in order to enhance the analgesic effect was investigated. The analgesic effect is due to the cessation or weakening of nerve impulses from the painful focus due to the elimination of hypoxia, the improvement of microcirculation, and the reduction of edema, it has been shown. Transcranial magnetic therapy is used as an analgesic tool in onconurology. The therapeutic anti-pain effect is associated with the stimulation of the antinociceptive system, an increase in the synthesis of natural analgesics — endorphins with their subsequent release into the cerebrospinal fluid and blood. As it has already been shown, with the increase in the intensity of pain and its duration, all indicators of the quality of life and the results of treatment of the patient deteriorate, so the search for ways to improve the antitumor effectiveness of specialized treatment and eliminate the causes that prevent their implementation continue to be relevant and in demand.